Opportunities and Challenges of Digital Media Ethics in the Age of Artificial Intelligence - Patphornchanat, Nuttraipat (Rajapark Journal, 2025)
This research aims to investigate the utilization of artificial intelligence (AI) in the media industry and its broad impact on audiences. Employing documentary research and in-depth interviews with experts in the broadcasting and television industry within the Bangkok metropolitan area from June to December 2024, the study reveals that AI has rapidly transformed the media landscape. This transformation affects all dimensions of the communication process (sender, message receiver, channel), presenting both opportunities and challenges. Particularly, the ethical challenges outweigh the opportunities, highlighting the necessity for regulatory oversight and public awareness. Key ethical concerns include copyright infringement, misinformation/disinformation, algorithmic bias, and privacy/security issues. Conversely, the opportunities presented by AI in the media industry encompass enhanced content efficiency, expanded communication channels, and the creation of more immersive media experiences. This research recommends that media regulatory bodies expedite the development of legal frameworks, policies, and ethical guidelines for the responsible use of AI. This includes the application of AI tools for content verification and filtering, as well as the promotion of media literacy among the public. Furthermore, media operators and independent content creators should actively participate in establishing ethical standards for AI utilization to ensure clear guidelines, facilitate accountability, and prevent ethical violations.